Analysis of the Impacts of Flypaper Effect on Comparative Poverty: A Comparative Study Based on the Financial Independence of Local Regions - Sihombing, Laurentius Vennock Parlindungan; Susilo (Journal of Development Economic and Social Studies, 2026)
The phenomenon of the flypaper effect is a topic that often receives significant attention in the context of regional finance. Issues regarding the level of regional financial independence are suspected to contribute to the existence of this phenomenon. This study aims to examine how the flypaper effect occurs and its impact on poverty through a comparison of regions classified by their level of financial independence during the period of 2015-2024 using path analysis methods. The results of this study demonstrate that in regions with low financial independence, the flypaper effect is present, whereas this phenomenon is not observed in regions with high financial independence. Furthermore, regional expenditures in both classifications fail to mediate the effect on poverty. Therefore, various reforms are necessary to prevent the occurrence of the flypaper effect and to improve the quality of regional spending towards a more ideal direction.